Effect of PRM1201 Combined With Adjuvant Chemotherapy on Preventing Recurrence and Metastasis of Stage III Colon Cancer: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial - Jia, Ru; Liu, Ningning; Cai, Guoxiang; Zhang, Yun; Xiao, Haijuan; Zhou, Lihong; Ji, Qing; Zhao, Ling; Zeng, Puhua; Liu, Huaimin; Huo, Jiege; Yue, Xiaoqiang; et al. (Frontiers in Oncology, 2021)
Background: Chemotherapy is the standard adjuvant treatment of colon cancer. Chinese herbal formula PRM1201 improves the efficacy of chemotherapy combined with Cetuximab or Bevacizumab in patients with metastatic colorectal cancer. This study aims to explore the benefits of treatment with chemotherapy plus PRM1201 in the postoperative adjuvant setting. Methods: In this parallel-group study, patients who had undergone curative resection for stage III colon cancer were randomly assigned to adjuvant chemotherapy (FOLFOX q2w for 6 months, or CapeOx q3w for 6 months) plus PRM1201 (chemo+PRM1201) or adjuvant chemotherapy plus placebo (chemo+placebo). The primary endpoint was disease-free survival (DFS), and the secondary endpoints were quality of life (QOL) and toxicity. Results: A total of 370 patients (chemotherapy plus PRM1201, n=184; chemotherapy plus placebo, n=186) were randomly assigned to each group. Until October 30, 2019, 96 events of recurrence, metastasis or death had been reported, of which 38 events were in the group given chemotherapy plus PRM1201 as compared with 58 events in the chemo+placebo group. Three-year DFS rates were 77.1% and 68.6% in the chemo+ PRM1201 and chemo+placebo group, respectively (hazard ratio [HR], 0.63; 95%CI, 0.42 to 0.94; P = 0.024). The QOL of patients in the chemo+PRM1201 group were significantly improved in terms of physical functioning and global quality of life, physical functioning, role functioning, emotional functioning, fatigue, and appetite loss (P < 0.05). The incidence of grade 3 or 4 TRAEs were similar between two arms. Conclusions: Combined with PRM1201 improved the adjuvant treatment of colon cancer. PRM1201 can be recommended as an effective option in clinical practice.